Polynomial Chaos and the Heave Motion of a Cylinder in Random Seas. Issue 1 (21st October 2015) - Kreuzer, Edwin; Solowjow, Eugen
Abstract The stochastic equation of motion for a heaving cylinder subject to irregular sea waves is solved numerically with the polynomial chaos framework. Thereby, the stochastic forcing is expressed by a truncated Karhunen‐Loève expansion and the hydrodynamic radiation is formulated as a state space model. We obtain the mean and the variance of the cylinder heave motion. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)